The impact of four family support programmes for people with a disability in Ireland - GRIFFITHS, COLIN; DE VRIES, JAN; DALY, LOUISE; HIGGINS, AGNES; SHEERIN, FINTAN; MCBENNETT, PADRAIG (My University, 2015)
Background: This article reports on an evaluation of four family support programmes in Ireland for families of people with a physical or an intellectual disability or autism. The focus of the evaluation, which took place within a year of the programmes’ completion, was on establishing whether the programmes had an impact on families’ capacity to effectively support their family member. Method: A mixed-method design was used, which included a survey (n ¼ 38) and interviews (n ¼ 19) with participating family members. Ethical approval for the study was given by the relevant university ethics committee. Results: Findings suggest that participation in the programmes enhanced knowledge, attitudes, and competencies of families and also impacted their ability to advocate for their family member and to connect with the community. Discussion and conclusions: Whilst outcomes were overwhelmingly positive, further follow-up would be required to ascertain if sustained capacity building took place.
PUBLISHED
Keywords: intellectual disability, family support, family-focused support, family-centred support, capacity building; intellectual disability, family support, family-focused support, family-centred support, capacity building; Inclusive Society